A Scientometric Study to a Critical Review on Promising Anticancer and Neuroprotective Compounds: Citrus Flavonoids - Mingyang Qiu; Wenlong Wei; Jianqing Zhang; Hanze Wang; Yuxin Bai; De-an Guo (MDPI AG, 2023)
Flavonoids derived from citrus plants are favored by phytomedicinal researchers due to their wide range of biological activities, and relevant studies have been sustained for 67 years (since the first paper published in 1955). In terms of a scientometric and critical review, the scientometrics of related papers, chemical structures, and pharmacological action of citrus flavonoids were comprehensively summarized. The modern pharmacological effects of citrus flavonoids are primarily focused on their anticancer activities (such as breast cancer, gastric cancer, lung cancer, and liver cancer), neuroprotective effects (such as anti-Alzheimer's disease, Parkinson's disease), and metabolic diseases. Furthermore, the therapeutic mechanism of cancers (including inducing apoptosis, inhibiting cell proliferation, and inhibiting cancer metastasis), neuroprotective effects (including antioxidant and anti-inflammatory), and metabolic diseases (such as non-alcoholic fatty liver disease, type 2 diabetes mellitus) were summarized and discussed. We anticipate that this review could provide an essential reference for anti-cancer and neuroprotective research of citrus flavonoids and provide researchers with a comprehensive understanding of citrus flavonoids.